COLEC10 is mutated in 3MC patients and regulates early craniofacial development. - Mustafa M Munye; Anna Diaz-Font; Louise Ocaka; Maiken L Henriksen; Melissa Lees; Angela Brady; Dagan Jenkins; Jenny Morton; Soren W Hansen; Chiara Bacchelli; Philip L Beales; Victor Hernandez-Hernandez (PLoS Genetics)
3MC syndrome is an autosomal recessive heterogeneous disorder with features linked to developmental abnormalities. The main features include facial dysmorphism, craniosynostosis and cleft lip/palate; skeletal structures derived from cranial neural crest cells (cNCC). We previously reported that lectin complement pathway genes COLEC11 and MASP1/3 are mutated in 3MC syndrome patients. Here we define a new gene, COLEC10, also mutated in 3MC families and present novel mutations in COLEC11 and MASP1/3 genes in a further five families. The protein products of COLEC11 and COLEC10, CL-K1 and CL-L1 respectively, form heteromeric complexes. We show COLEC10 is expressed in the base membrane of the palate during murine embryo development. We demonstrate how mutations in COLEC10 (c.25C>T; p.Arg9Ter, c.226delA; p.Gly77Glufs*66 and c.528C>G p.Cys176Trp) impair the expression and/or secretion of CL-L1 highlighting their pathogenicity. Together, these findings provide further evidence linking the lectin complement pathway and complement factors COLEC11 and COLEC10 to morphogenesis of craniofacial structures and 3MC etiology.